The effects of probiotics and symbiotics on risk factors for hepatic encephalopathy - Viramontes Hörner, Daniela; Avery, Amanda; Stow, Ruth (Lippincott, Williams & Wilkins:, 2017)
Alterations in the levels of intestinal microbiota, endotoxemia, and inflammation are novel areas of interest in the pathogenesis of hepatic encephalopathy (HE). Probiotics and symbiotics are a promising treatment option for HE due to possible beneficial effects in modulating gut microflora and might be better tolerated and more cost-effective than the traditional treatment with lactulose, rifaximin or L-ornithine-L-aspartate. A systematic search of the electronic databases PubMed, ISI Web of Science, EMBASE, and Cochrane Library was conducted for randomized controlled clinical trials in adult patients with cirrhosis, evaluating the effect of probiotics and symbiotics in changes on intestinal microflora, reduction of endotoxemia, inflammation, and ammonia, reversal of minimal hepatic encephalopathy (MHE), prevention of overt hepatic encephalopathy (OHE), and improvement of quality of life. Nineteen trials met the inclusion criteria. Probiotics and symbiotics increased beneficial microflora and decreased pathogenic bacteria and endotoxemia compared with placebo/no treatment, but no effect was observed on inflammation. Probiotics significantly reversed MHE [risk ratio, 1.53; 95% confidence interval (CI): 1.14, 2.05; P=0.005] and reduced OHE development (risk ratio, 0.62; 95% CI: 0.48, 0.80; P=0.0002) compared with placebo/no treatment. Symbiotics significantly decreased ammonia levels compared with placebo (15.24; 95% CI: −26.01, −4.47; P=0.006). Probiotics did not show any additional benefit on reversal of MHE and prevention of OHE development when compared with lactulose, rifaximin, and L-ornithine-L-aspartate. Only 5 trials considered tolerance with minimal side effects reported. Although further research is warranted, probiotics and symbiotics should be considered as an alternative therapy for the treatment and management of HE given the results reported in this systematic review.